Glucose transporters as markers of diagnosis and prognosis in cancer diseases - Leszek Szablewski (Frontiers Media S.A., 2022)
Glucose is a main metabolic substrate, which plays a role as a source of energy and a substrate in several processes. Cell membrane is lipophilic, whereas monosaccharides are hydrophilic. Therefore, lipid bilayer is impermeable for these substances and they need specific carrier proteins. Glucose metabolism in cancer cells differs from this process in normal cells. Cancer cells prefer the process of glycolysis, which generates less molecules of ATP than complete oxidative breakdown, therefore cancer cells need more molecules of glucose. Increased uptake of glucose is due to changes in expression of glucose transporters. Several glucose transporters are overexpressed in cancer cells, however, there are also observed decreased levels of these proteins in cancer cells. There are observed specific correlations between cancer and expression of glucose carrier proteins. Therefore, changes in expression of glucose transporters in cancers may be treated as a marker of diagnosis and/or prognosis for cancer patients.